Analisis Kemandirian Belajar Siswa Dalam Pembelajaran Tematik Kelas V SD Negeri 11 Muara Telang - Anisa Anisa; Farhan Yadi; Aldora Pratama (Departement of Mathematics Education, 2023)
This study aims to determine the learning independence of grade V students of SD Negeri 11 Muara Telang in thematic learning. This research was carried out at SD Negeri 11 Muara Telang in grade V of the 2022/2023 school year. The approach in this study is a qualitative approach, with a descriptive method, which is supported by field assessments and references related to the theme discussed. Data collection techniques use observation, interviews, questionnaires and documentation. Data is analyzed by means of reduction, display and generalization or inference. Based on the results of the study, it can be concluded that the learning independence of students at SD Negeri 11 Muara Telang has developed well. Students have high independence. Indicators of learning independence include confidence, active in learning, discipline in learning and responsibility in learning. Students who have high learning independence will try to complete tasks with their own abilities.